APLIKASI SPELLING CORRECTING PADA PENULISAN BAHASA INDONESIA DENGAN METODE JARO WINKLER - Samudero, Fauzan Risang Agung; Jati Sasongko Wibowo (STEKOM PRESS, 2024)
Typing errors in documents are fairly common. The process of checking typing errors manually will take a lot of time. Therefore, a system called Indonesian spelling correcting with Jaro Winkler is needed. Spelling Correcting is a feature that can check and correct word writing errors automatically. Jaro Winkler is an algorithm used for the word correction process by calculating the value obtained from the results of the operation of modifying one word with another word with the help of a matrix. Based on the results of trials on 13 words, namely